The Sea of Marmara during Marine Isotope Stages 5 and 6 - Çağatay, M. Namik; Eriş, K. Kadir; Makaroğlu, Özlem; Yakupoğlu, Nurettin; Henry, Pierre; Leroy, Suzanne A.G.; Uçarkuş, Gülsen; Sakinç, Mehmet; Yalamaz, Burak; Bozyiğit, Cerennaz; Kende, Julia (Elsevier BV, 2019)
Abstract Multi-proxy analyses and lithology of two cores, MRS-CS18 and MRS-CS27, from the Imrali Basin of the Sea of Marmara (SoM) provide novel information on environmental conditions, relative sea level, and sill depths of the straits of Bosporus and Dardanelles during the Marine Isotope Stages (MIS) 5 and 6. The fossil and multi-proxy geochemical records show that lacustrine conditions prevailed in the SoM during most of MIS 6, from 171 to 134 ka BP, and that the transition to marine conditions during Termination II took place at ∼134.06 ± 1.10 ka BP. MIS 5 interstadials a, c, and e witnessed the formation of three sapropels (MSAP-2, MSAP-3 and MSAP-4) under suboxic to anoxic marine conditions, whereas during stadials MIS 5b (∼94–86) and MIS 5d (∼112–105 ka BP), lacustrine and marine conditions with deposition of sediments having relatively low TOC contents ( The SoM geochemical proxy records correlate well with the regional terrestrial and marine records and the NGRIP oxygen isotope record with its Stadial and Interstadial phases, showing the common effect of the North Atlantic climatic events triggered by the perturbations in the Atlantic Meridional Overturning Circulation. However, the amplitude of the oscillations recorded in the SoM during MIS 6 (Penultimate Glacial Period) is relatively small compared to the MIS 4 to MIS 2 (Last Glacial Period).
Keywords: Sea of Marmara; Sedimentology-marine cores; [SDU.STU]Sciences of the Universe [physics]/Earth Sciences; Marine isotope stages 5-6; Eastern Europe; Late Quaternary; Marine Isotope stages 5-6; Geochemical proxies; Paleoceanography; [SDU.STU.GC]Sciences of the Universe [physics]/Earth Sciences/Geochemistry; [SDU.STU.ST]Sciences of the Universe [physics]/Earth Sciences/Stratigraphy; [SDU.STU.GC] Sciences of the Universe [physics]/Earth Sciences/Geochemistry; [SDU.STU] Sciences of the Universe [physics]/Earth Sciences; [SDU.STU.ST] Sciences of the Universe [physics]/Earth Sciences/Stratigraphy; Sapropels; Late quaternary